Analysis and evaluation of sustainable socio-economic development of Azerbaijan - Guliyev Zakir Gasham (Reviews of Modern Science, 2024)
One of the global challenges facing the humanity in the 21st century is to improve the sustainable socio-economic development of countries. Thus, significant results have been achieved in Azerbaijan's socio-economic development over the past decade. The main reason for this is the implementation of large economic projects to ensure continued development in Azerbaijan. Innovative development of the economy is associated with the solution of the problem of promotion of innovation, the formation and development of innovative entrepreneurship, fundamental tax reforms and elimination of staff shortages in this area. The most important thing here is that the future state of the Republic of Azerbaijan will find the key government program "Strategic roadmap for key sectors of the national economy". The socio-economic successes of Azerbaijan in recent years have also been reflected in the reports of reputable international rating agencies. Azerbaijan has been included in the top 20 reformist countries in the World Bank's Doing Business rating. In total, it ranks 34th out of 190 countries. The country is ranked ninth according to the Business Establishment Index. In this report, Azerbaijan entered the top five in the world in terms of starting a business by simplifying business registration and was ranked as one of the best practice countries.[17] President Ilham Aliyev said at a conference on the results of the first year of implementation of the “State Program on socio-economic development of the regions of the Republic of Azerbaijan for 2019-2023”. to raise the level of competitive states. Therefore, given the challenges of the modern world, rapid development in the region will continue. Taking into account all these pressing scientific issues, the article has become a research problem in the field of industry, agriculture, entrepreneurship and innovation in terms of effective implementation of the strategic roadmap and the importance of sustainable socio-economic development of Azerbaijan in general.